1998
DOI: 10.1002/(sici)1096-9861(19980824)398:2<151::aid-cne1>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Neural connections of the pineal organ in the primitive bony fish Acipenser baeri : A carbocyanine dye tract‐tracing study

Abstract: The pineal organ of the sturgeon (Acipenser baeri; Chondrostei) consists of an elongated terminal vesicle and a long stalk that runs to the region of the posterior commissure. In order to investigate the neural connections of the pineal organ of the surgeon, a fluorescent indocarbocyanine (DiI) was applied to the pineal stalk of paraformaldehyde-fixed brains. This application strongly labeled the pineal tracts (right and left), which form an extensive bilateral projection to the brain. The fibers of these trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Present results show the presence of a GABAergic population of multipolar efferent neurons in the pineal organ of the sturgeon. Pinealofugal projections of the sturgeon pineal were already traced to some centers of the diencephalon and midbrain using DiI labeling (Yáñez & Anadón, 1998), but the actual targets of GABAergic pinealofugal fibers are not known. The presence of GABAergic projection neurons was also reported in the pineal organ of lampreys (Pombal et al., 1999) and sharks (Carrera et al., 2006), where they are multipolar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present results show the presence of a GABAergic population of multipolar efferent neurons in the pineal organ of the sturgeon. Pinealofugal projections of the sturgeon pineal were already traced to some centers of the diencephalon and midbrain using DiI labeling (Yáñez & Anadón, 1998), but the actual targets of GABAergic pinealofugal fibers are not known. The presence of GABAergic projection neurons was also reported in the pineal organ of lampreys (Pombal et al., 1999) and sharks (Carrera et al., 2006), where they are multipolar.…”
Section: Discussionmentioning
confidence: 99%
“…The organization of the sturgeon brain is mainly known from morphological studies with classical neuroanatomical methods (Golgi methods: Johnston, 1898, 1901; Nissl methods: Nieuwenhuys, 1998; Rupp & Northcutt, 1998) and tract‐tracing studies (Albert et al., 1999; Huesa et al., 2003, 2006; New & Bodznick, 1985; New & Northcutt, 1984a; New & Northcutt, 1984b; Northcutt, 2011; N. Yamamoto et al., 1999; Yáñez & Anadón, 1998). Immunohistochemical studies in the brain of sturgeons have reported the organization of the monoaminergic and cholinergic systems (Adrio et al., 1999, 2000, 2002; Piñuela & Northcutt, 2007) as well as that of some peptidergic systems (Adrio et al., 2005, 2008; Baker & Bird, 2002; González et al., 1992; Leprêtre et al., 1993).…”
Section: Introductionmentioning
confidence: 99%